Mahatma Gandhi’s Philosophy of Non-Violence: The Foundation of Global Peace in the 21st Century: महात्मा गांधी का अहिंसा दर्शन: 21वीं सदी की वैश्विक शांति-स्थापना का आधार - Chamoli, Amit; Kundariya, Madhu (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The global landscape of the 21st century is struggling with serious challenges such as political instability, terrorism, wars, climate change, pandemics, and social inequality. In this context, Mahatma Gandhi’s philosophy of non-violence is not merely a historical legacy but emerges as a practical and meaningful guide for contemporary humanity. Gandhi firmly believed that violence can never solve any problem; on the contrary, non-violence, grounded in truth, compassion, coexistence, and moral strength, can lay the foundation for lasting world peace. The study concludes that Gandhi’s ideas were not confined to the Indian freedom struggle but remain equally relevant today for global peace and human welfare. His statement— “The earth provides enough to satisfy every man’s need, but not every man’s greed”—offers profound guidance in the context of modern consumerism and ecological imbalance. Thus, Gandhi’s philosophy of non-violence can be recognized as a strong, ethical, and practical foundation for global peacebuilding in the 21st century. Abstract in Hindi Language: इक्कीसवीं सदी का वैश्विक परिदृश्य राजनीतिक अस्थिरता, आतंकवाद, युद्ध, जलवायु परिवर्तन, महामारी और सामाजिक असमानता जैसी गंभीर चुनौतियों से जूझ रहा है। ऐसे परिदृश्य में महात्मा गांधी का अहिंसा दर्शन केवल ऐतिहासिक विरासत नहीं, बल्कि समकालीन मानवता के लिए एक व्यावहारिक और जीवनोपयोगी मार्गदर्शक के रूप में उभरता है। गांधी का दृढ़ विश्वास था कि हिंसा किसी भी समस्या का समाधान नहीं हो सकती; इसके विपरीत, सत्य, करुणा, सह-अस्तित्व और नैतिक आत्मबल पर आधारित अहिंसा ही विश्व शांति की स्थायी नींव रख सकती है। अध्ययन से यह निष्कर्ष सामने आता है कि गांधी के विचार केवल भारतीय स्वतंत्रता संग्राम तक सीमित नहीं थे, बल्कि वे आज भी विश्व शांति और मानव कल्याण के लिए उतने ही प्रासंगिक हैं। उनका कथन— “धरती पर हर किसी की ज़रूरत के लिए पर्याप्त है, लेकिन किसी के लालच के लिए नहीं”— आधुनिक उपभोक्तावाद और पर्यावरणीय असंतुलन के संदर्भ में गहन मार्गदर्शन प्रदान करता है। अतः गांधी का अहिंसा दर्शन इक्कीसवीं सदी की वैश्विक शांति-स्थापना के लिए एक सुदृढ़, नैतिक और व्यावहारिक आधार के रूप में स्वीकार किया जा सकता है। Keywords: अहिंसा दर्शन, गांधी, वैश्विक शांति, वैश्विक व्यवस्था, 21वीं सदी